2020
DOI: 10.1002/app.49508
|View full text |Cite
|
Sign up to set email alerts
|

Eggshell membrane reinforced polypropylene biocomposite and its tactile assessment

Abstract: Considering the better tactile performance (pleasantness) of different materials for example, leather, fur, feather, and so on, which are known to be the tribopositive materials, herein, the tribo‐positive eggshell membrane (ESM) powders derived from waste eggshell were melt‐mixed with polypropylene (PP) to prepare a low‐cost ESM/PP biocomposite of enhanced tactile property. In this regard, in‐plane coefficient of friction (COF) has been examined and found a decreasing trend with increasing the ESM content whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Of course, there are also some reports in the literature on other types of soft-feel materials. For example, Na et al considered that leather, fur, feathers, and other materials used as friction-positive electrode materials had good tactile properties (comfort) [19]. Therefore, they melted and mixed eggshell membrane (ESM) powders, which were also friction-positive electrode materials, with PP and found that the prepared ESM/PP biocomposite materials had enhanced tactile properties.…”
Section: The Basic Composition Of Pu Soft Feel Materialsmentioning
confidence: 99%
“…Of course, there are also some reports in the literature on other types of soft-feel materials. For example, Na et al considered that leather, fur, feathers, and other materials used as friction-positive electrode materials had good tactile properties (comfort) [19]. Therefore, they melted and mixed eggshell membrane (ESM) powders, which were also friction-positive electrode materials, with PP and found that the prepared ESM/PP biocomposite materials had enhanced tactile properties.…”
Section: The Basic Composition Of Pu Soft Feel Materialsmentioning
confidence: 99%
“…ESM is a residual and accessible material that exhibits triboelectrification and piezoelectrification properties, being applied as a separator in lithium-ion batteries, electrodes in supercapacitors, tribomaterial in TENG, tissue for regeneration membranes, a therapeutic agent for tissue disorders, water purification membrane, green energy source, , and so on. This biomaterial is composed of a biopolymeric structure, mainly of collagen (types I, V, and X), which represents up to 96% of its dry weight, along with other bioactive compounds such as chondroitin sulfate, hyaluronic acid, and sulfur-rich proteins. ,, …”
Section: Introductionmentioning
confidence: 99%